2019
DOI: 10.1016/j.gpb.2019.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Tung Tree (Vernicia Fordii) Genome Provides A Resource for Understanding Genome Evolution and Improved Oil Production

Abstract: Tung tree (Vernicia fordii) is an economically important woody oil plant that produces tung oil rich in eleostearic acid. Here, we report a high-quality chromosome-scale genome sequence of tung tree. The genome sequence was assembled by combining Illumina short reads, Pacific Biosciences single-molecule real-time long reads, and Hi-C sequencing data. The size of tung tree genome is 1.12 Gb, with 28,422 predicted genes and over 73% repeat sequences. The V. fordii underwent an ancient genome triplication event s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 57 publications
3
48
0
Order By: Relevance
“…Castor bean and Mercurialis annua clustered together, both members of subfamily Acalyphoideae, and diverged from four other members of Euphorbiaceae (subfamily Crotonoideae) ~ 48.28 MYA (Fig. 1 c), consistent with previous reports [ 20 , 21 ]. Both Ks (synonymous substitution rate) and 4DTv (fourfold synonymous third codon transversion) analyses reveal that V. fordii , J. curcus , and castor bean share the ancient whole-genome triplication (γ) with Vitis , while for H. brasiliensis and M. esculenta experienced a recent species-specific duplication (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Castor bean and Mercurialis annua clustered together, both members of subfamily Acalyphoideae, and diverged from four other members of Euphorbiaceae (subfamily Crotonoideae) ~ 48.28 MYA (Fig. 1 c), consistent with previous reports [ 20 , 21 ]. Both Ks (synonymous substitution rate) and 4DTv (fourfold synonymous third codon transversion) analyses reveal that V. fordii , J. curcus , and castor bean share the ancient whole-genome triplication (γ) with Vitis , while for H. brasiliensis and M. esculenta experienced a recent species-specific duplication (Fig.…”
Section: Resultssupporting
confidence: 91%
“…For example, during the biosynthesis of tung oil in seeds of the tung tree (Venicia fordii), the contents of LA and ALA are higher in young seed and gradually decrease as seed matures. Correspondingly, DGAT2 and PDAT are highly expressed in the earlier stages of seed development in this latter species 45 . In this current study, the transcripts of DGAT1and PDAT1 (Unigene0020593 and Unigene0016056, respectively) were upregulated in mature seed (SI-5) (Fig.…”
Section: Discussionmentioning
confidence: 84%
“…The grape species (Vitis vinifera) only experienced this ancient whole-genome triplication event without any additional wholegenome duplications. The γ whole-genome triplication was later confirmed to have occurred in different species, such as papaya, coffee, cocoa, peach, tung tree and hardy rubber tree (Argout et al, 2011;Denoeud et al, 2014;International Peach Genome et al, 2013;Jaillon et al, 2007;Tang et al, 2008;Wuyun et al, 2018;Zhang, Liu, et al, 2019). A broader sampling and analyses using orthologs suggested that the whole-genome triplication occurred before the divergence of the rosids and asterids and after the separation of F I G U R E 1 Species richness and polyploidy events in the flowering plants.…”
Section: An Ancient Wave Of Paleopolyploidy Events In Angiosperms Omentioning
confidence: 97%